The Influencing Factors of Bacterial Resistance Related to Livestock Farm: Sources and Mechanisms - Guo, Kaixuan; Zhao, Yue; Cui, Luqing; Cao, Zhengzheng; Zhang, Fan; Wang, Xiangru; Feng, Jiawei; Dai, Menghong (Frontiers in Animal Science, 2021)
Bacterial resistance is a complex scientific issue. To manage this issue, we need to deeply understand the influencing factors and mechanisms. Based on the background of livestock husbandry, this paper reviews the factors that affect the acquisition of bacterial resistance. Meanwhile, the resistance mechanism is also discussed. "Survival of the fittest" is the result of genetic plasticity of bacterial pathogens, which brings about specific response, such as producing adaptive mutation, gaining genetic material or changing gene expression. To a large extent, bacterial populations acquire resistance genes directly caused by the selective pressure of antibiotics. However, mobile resistance genes may be co-selected by other existing substances (such as heavy metals and biocides) without direct selection pressure from antibiotics. This is because the same mobile genetic elements as antibiotic resistance genes can be co-located by the resistance determinants of some of these compounds. Furthermore, environmental factors are a source of resistance gene acquisition. Here, we describe some of the key measures that should be taken to mitigate the risk of antibiotic resistance. We call on the relevant governments or organizations around the world to formulate and improve the monitoring policies of antibiotic resistance, strengthen the supervision, strengthen the international cooperation and exchange, and curb the emergence and spread of drug-resistant strains.